Effect of ruminal protozoa on performance of early-weaned calves - K.L. Anderson; Tiruvoor G. Nagaraja; J.L. Morrill; P.G. Reddy (Kansas Agricultural Experiment Station Research Reports, 1987)
Twenty newborn bull calves assigned to two groups, protozoa-free or protozoa-inoculated, were used to determine the effects of ruminal protozoa on performance of early weaned calves. Calves in the protozoa group were inoculated via stomach tube with a suspension of ruminal protozoa at weekly intervals until a viable population was established. Calves were evaluated weekly for weight gain and feed intake. Feed intake and weight gain were not significantly different between the groups but tended to be higher in protozoa-inoculated than protozoa-free calves.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Ruminal protozoa; Performance; Growth; Feed intake; Weight gain